Development and comparison of standardized bacterial metabolite profiles by hyphenated planar chromatography for characterization of feed additives and probiotic feeds - Kruse, Stefanie; Justus Liebig University Giessen (My University, 2022)
In animal production, AGP were used for several decades to improve animal growth and FCRs as well as to reduce morbidity and mortality of the animals. However, in 2006, the European Union banned the use of several AGPs due to the increased antibiotic resistance of infectious human pathogens. Probiotics seem to be an effective alternative to replace growth-promoting agents but up to now their mode of action is not fully understood. Imaging HPTLC with upstream cultivation proved to be an excellent method to characterize the metabolic profiles of the probiotic B. s. 29784, compared to those of genetically similar bacteria. Due to the various detection capabilities, the method enabled a better understanding of the probiotic effect. Special characteristics in the metabolic profile of the probiotic, such as the production of bioactive or antimicrobial metabolites, were described and a target metabolite, such as the lipopeptide surfactin, was identified. In the animal gut, the probiotic bacteria interacts with several other bacteria that could affect the metabolic profile of probiotics. Imaging HPTLC with upstream cultivation of bacteria in a co-culture proved the influence of this interaction by inoculation of E. coli (common pathogen) together with the probiotic. The results explain the sometimes contradictory observations of different probiotics in industrial use and the need for controlled conditions for the application of probiotics. In industrial quality control, cell counting is the most common method to determine the cell number of probiotics in feed. However, the results only describe the number of CFU/kg in the feed and do not determine the amount of probiotic spores. In the last decades, scientists in the field of probiotic research assumed that specific metabolites of the probiotic are responsible for the positive effect. Based on imaging HPTLC, a new method was developed to quantify spores of the probiotic in feed based on a non-specific metabolite. The validation of this method showed excellent results. Thus, imaging HPTLC offers the possibility of precise and accurate quantification of spores in feeds. Furthermore, in the probiotic B. s. 29784 a specific metabolite was detected (tested against high genetically similar bacteria) under the analyzed cultivation condition. For specific quantification of the probiotic in feed, the new developed and validated HPTLC method was adapted to this metabolite. In conclusion imaging HPTLC can be used to characterize bacterial metabolic profiles, such as probiotics, monitor bacterial interactions, and quantify the amount of probiotic spores in feed.
Keywords: HPTLC; high-performance thin-layer chromatography; metabolic profiling; Bacillus subtilis; ddc:500